2019
DOI: 10.1016/j.jhlste.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and barriers that females face for study and employment in sport

Abstract: The lack of women in graduate-level jobs in sport may be because of a lack of supply. Based on data from the Universities and Colleges Admissions Service for the UK (UCAS, 2017), the number of females applying and being accepted onto sport and exercise science courses is low. These figures are also decreasing. In 2016, 29% of applicants were female, compared to in 2007, when 34% were female; the same percentages were observed for acceptances (UCAS, 2017). In the US, there is a distinct lack of gender diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 52 publications
0
39
0
3
Order By: Relevance
“…The physiological construction of the female body comprises less skeletal frame and muscle mass than males [ 22 ]. That fact might reduce self-efficacy in performing PA for Thai females [ 23 ]. In addition, there is a socio-cultural expectation for Thai females to be calm and neat, and the normative Thai preference for fair skin may deter many women from outdoor, daytime PA [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The physiological construction of the female body comprises less skeletal frame and muscle mass than males [ 22 ]. That fact might reduce self-efficacy in performing PA for Thai females [ 23 ]. In addition, there is a socio-cultural expectation for Thai females to be calm and neat, and the normative Thai preference for fair skin may deter many women from outdoor, daytime PA [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…En la literatura consultada se encontró que la falta de experiencia, saturación del mercado laboral, puestos con baja remuneración económica, personas no calificadas o pasantes que ocupan espacios laborales propios de la EF y la falta de especialización, son algunas de las dificultades que enfrentan los recién egresados para poder conseguir un empleo (Salles et al, 2015). Aunado a lo anterior, encontrar trabajo representa un reto aún mayor para las mujeres, debido a diversas barreras ideológicas sobre su desempeño profesional en ciertas áreas de la EF (Forsyth, Jones, Duval & Bambridge, 2019;Sykes, 2004). Una vez que obtienen empleo enfrentan desventajas salariales, por tal motivo es común encontrar menos mujeres desempeñándose profesionalmente en el campo de EF (Fonseca & Both, 2021;Rodeiro et al, 2018).…”
Section: Inserción Laboral Del Egresadounclassified
“…Relevant studies that are necessary to set out the outset of the study are reported in this article. Avalanche of published literature can be witnessed on women development across the globe including: identifying the capabilities of women's leadership and sustainable development in Colombia (Barrios et al, 2020), exploring the relationship between female directorship and firm performance in France (Bennouri et al, 2018), gender inequality in assets ownership in Latin America (Deere et al, 2010), wage gaps of female-male among salaried workers in India (Deshpande et al, 2018;Lee & Wie, 2017;Menon & Rodgers, 2009), uncovered opportunities and barriers of female employment in sports in UK (Forsyth et al, 2019), women segregation in tourism employment in APEC region (Hutchings et al, 2020), women empowerment in East Africa (Miedema et al, 2018), women empowerment in Nepal (O'Hara & Clement, 2018), women asset ownership in rural south-east and north-east Nigeria (Oladokun et al, 2018), participation of Saudi women in development index (Omair et al, 2020), gender wage gap in Mexico (Popli, 2013), gender wage discrimination in Pakistan (Sabir & Aftab, 2007;Yasmin, 2009), gender wage inequality between 1992-2014 in Sri Lanka (Seneviratne, 2020), role of female directors and stock price in China (Shahab et al, 2020), women's social and financial empowerment in Pakistan (Tahir et al, 2018) and gender wage gap in Philippines (Zveglich Jr. et al, 2019). Bennouri et al (2018) examined the data of 394 French firms and affirmed that there is a positive relationship between female board directorship and firm performance; similar finding have been found by Nekhili & Gatfaoui (2013) and Peni (2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Deshpande et al (2018) found male-female wage discrimination among salaried workers in India wherein female are likely to be paid less. Forsyth et al (2019) identified barriers and opportunities of female employment in sports and bolstered that gender inequality is still need to be addressed in educational sports related settings. Hutchings et al (2020) gathered data form tourism sector of 21 Asia-Pacific Economic Cooperation (APEC) member economies and concluded that there is clear segregation of women in tourism employment across the economies due to intersectionality and cultural barriers.…”
Section: Literature Reviewmentioning
confidence: 99%